Authors Index: COBEC 2012 - 2st Brazilian Congress in Electromyography and Kinesiology; 2st National Meeting of Myotherapy Procedures - Piracicaba Dental School UNICAMP (Universidade Estadual de Campinas, 2010)
All abstracts appear as submitted by the authors without editing.